Ideas and Practices for the Social Management of Territories of Citinzenship.: The Case of the Borborema Territory, Paraiba (Sustainability in Debate, 2013)
The Territories of Citizenship Program aims to strengthen small-scale farmers in Brazil by financingproductive projects and infrastructures defined within deliberative institutional arrangementswhich is implementing the so-called “cycle of social management”. It presupposes dialectic active and progressive between the social capital of the territory, collective participation and projectimplementation, resulting in a virtuous process and sustainable rural development. The Territoryof Borborema, in the state of Paraiba, was created in 2003 with a high level of social capital andone process of consolidation ofpeasant social movements and agroecological transition. However,it does not show a good performance in terms of implementation of investment projects. Thispaper analyse this apparent paradox making relationship between the ideology of the governmentand the practice of social actors within the territorial device.